2020
DOI: 10.1186/s12916-020-01830-4
|View full text |Cite
|
Sign up to set email alerts
|

Disability, psychological distress and quality of life in relation to cancer diagnosis and cancer type: population-based Australian study of 22,505 cancer survivors and 244,000 people without cancer

Abstract: Background Improved survival means that cancer is increasingly becoming a chronic disease. Understanding and improving functional outcomes are critical to optimising survivorship. We quantified physical and mental health-related outcomes in people with versus without cancer, according to cancer type. Methods Questionnaire data from an Australian population-based cohort study (45 and Up Study (n = 267,153)) were linked to cancer registration data to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 125 publications
4
56
0
Order By: Relevance
“…Previous studies supported our ndings. A large population-based study consisting of 266505 cases showed low physical function, distress and reduced QoL were more common among cancer patients than in people without cancers (15). Particularly, Shin et al compared the QoL of 331 urologic cancer survivors and 1177 healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies supported our ndings. A large population-based study consisting of 266505 cases showed low physical function, distress and reduced QoL were more common among cancer patients than in people without cancers (15). Particularly, Shin et al compared the QoL of 331 urologic cancer survivors and 1177 healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…An additional measure included in the present study is the K10 (Kessler et al, 2002;. This is because the K10 has been, and continues to be, one of the most popular psychological distress measures in the literature (Some examples: Every-Palmer et al, 2020;Furukawa et al, 2003;Joshy et al, 2020;Lace et al, 2019;Nagel et al, 2020;Slade et al, 2011). In our study, we expected the K10 to be strongly positively associated with the DASS-21, and strongly negatively associated with the BEES balanced score.…”
Section: Dass-21 and K10mentioning
confidence: 90%
“…Higher scores indicate a better QoL (36,37). For secondary outcomes, patients' health literacy was assessed by means of a validated assessment tool (HLS-EU-Q6 (38), score ranges between 1 and 4; score is grouped into insu cient (1-2 score), problematic (2-3 scores), and su cient (3)(4)). The relationship between physicians and patients was measured by the quality of the doctor-patient communication using an adapted version of the PRA-D (score ranges from 5 to 35; higher scores indicate better doctor-patient communication) (39).…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
“…Oncological diseases are prevalently associated with mental disorders such as depression, anxiety disorders and insomnia (2,3). Depending on the type of cancer and the stage of the disease, there is also a high incidence of disability, which also contributes to a low quality of life (4). Medical care of psychosocial burdens of disease in the context of a cancer diagnosis are heterogeneously dealt with and distinct services are provided.…”
Section: Introductionmentioning
confidence: 99%